Wideband Absorbance Outcomes in Newborns: A Comparison With High-Frequency Tympanometry, Automated Brainstem Response, and Transient Evoked and Distortion Product Otoacoustic Emissions. Issue 5 (September 2015) - Aithal, Sreedevi; Kei, Joseph; Driscoll, Carlie; Khan, Asaduzzaman; Swanston, Andrew
Abstract : Objectives: The purpose of this study was to evaluate the test performance of wideband absorbance (WBA) in terms of its ability to predict the outer and middle ear status as determined by nine reference standards. Design: Automated auditory brainstem response (AABR), high-frequency (1000 Hz) tympanometry (HFT), transient evoked otoacoustic emission (TEOAE), and distortion product otoacoustic emission (DPOAE) tests were performed on 298 ears (144 right, 154 left) of 192 (108 males, 84 females) neonates with a mean age of 43.7 hours (SD = 21.3, range = 8.3 to 152.2 hr). WBA was measured from 0.25 to 8 kHz using clicks under ambient pressure conditions. Test performance of WBA was assessed in terms of its ability to identify conductive conditions in neonates when compared with nine reference standards (including four single tests and five test batteries) using the receiver operating characteristic analysis. Results: The test performance of WBA against the test battery reference standards was better than that against single test reference standards. The area under the receiver operating characteristic curve reached a high value of 0.78 for HFT + TEOAE + DPOAE and AABR + TEOAE + DPOAE reference standards. Within the ears that passed each of the reference standards, there were no significant differences in WBA. However, for the ears that failed each of the test standards, there were significant differences in WBA. The region between 1 and 4 kHz provided the best discriminability to evaluate the conductive status compared with other frequencies. Conclusions: WBA is a desirable measure of conductive conditions in newborns due to its high performance in classifying ears with conductive loss as determined by the best performing surrogate gold standards (HFT + TEOAE + DPOAE and AABR + TEOAE + DPOAE). Abstract : Use of distortion product otoacoustic emissions (DPOAEs) as a reference standard for middle ear function limits the clinical applicability of wideband absorbance. This study compared the test performance of wideband absorbance against four single tests and five test batteries in terms of its ability to predict the outer and middle ear status in 298 ears of 192 neonates. The test performance of wideband absorbance against the test battery reference standards was better than that against single test reference standards including DPOAEs.